Highly Photoluminescent Carbon Dots Derived from Discarded Chewing Gum: toward Multiple Sensing of pH, Ferric Ion, and Adenosine Triphosphate. Issue 43 (26th November 2019) - Hu, Yaoping; Gao, Zhijin
Abstract: In this paper, we develop a sustainable strategy to reuse discarded chewing gum for low‐cost synthesis of carbon dots (CDs) via a H2 O2 ‐assisted hydrothermal method. The as‐prepared CDs have a large photoluminescence (PL) quantum yield (QY) of up to 25.7%, much higher than the most values of waste‐derived CDs. Interestingly, the PL intensity of CDs increases linearly as pH rises from 1 to 6, demonstrating the possibility of CDs for accurate pH monitoring in acidic conditions. It is suggested that the pH‐responsive PL feature is induced by the protonation and deprotonation of the surface oxygenous groups of CDs. Through the fluorescence quenching and recovery processes, the CDs can serve as a selective and sensitive sensor for sequential detection of ferric ion (Fe 3+ ) and adenosine triphosphate (ATP) with limit of detection (LOD) as low as 0.028 and 0.003 μM, respectively. A possible electron transfer process is proposed to elucidate the sensing mechanism. For real applications, the CD sensing platform is successfully employed to determinate pH in natural stream, Fe 3+ in tap water, and ATP in erythrocyte sample. Abstract : This work demonstrates the reuse of discarded chewing gum as a promising carbon source for clean and low‐cost synthesis of highly photoluminescent carbon dots (CDs) via a H2 O2 ‐assisted hydrothermal method. The as‐prepared CDs can serve as a fluorescence sensing platform for sensitive detection of pH, Fe 3+, and adenosine triphosphate (ATP) in complex environmental and biological samples. The potential sensing mechanisms are proposed.